The Strategy of Aqidah Akhlak Teachers in Addressing the Negative Impact of the TikTok Application on Students - M Sholahuddin (Penerbit Hellow Pustaka, 2025)
Instilling noble morals and ethics, supervision and guidance, role models, carrying out positive activities, rules, giving awards and sanctions as strategies to overcome the negative impacts of the Tiktok application among students of Mts Al-Fadlaly, Probungan, Klampis, this aims to accustom students to avoid unwanted bad impacts, motivate students to continue to grow their faith and piety to Allah SWT. This study uses a qualitative research method with a descriptive approach that explains the strategies of aqidah and moral teachers in overcoming the negative impacts of the Tiktok application with a total of 122 students as the population and several students taken as samples. Based on the results of the analysis that has been carried out in this study, the strategy in fostering and instilling noble morals and ethics can overcome the negative impacts of the Tiktok application watched by students so that students become better than before. Not only that, students also apply honesty and self-awareness in everyday life. Thus, the instillation of noble morals and ethics, as well as the role models given by teachers and students are strategies in overcoming the negative impacts of the Tiktok application among students, which are quite satisfying and make it easier for teachers to educate and shape noble moral characters for their students.